Preparation and thermal energy storage studies of CH3COONa·3H2O–KCl composites salt system with enhanced phase change performance. (5th June 2016) - Li, Xiang; Zhou, Yuan; Nian, Hongen; Zhu, Fayan; Ren, Xiufeng; Dong, Ouyang; Hai, Chunxi; Shen, Yue; Zeng, Jinbo
Graphical abstract: Highlights: The phase change temperature range of CH3 COONa·3H2 O–KCl was between 50 °C and 58 °C. The mechanism of phase change temperature was explained by quantum chemical calculations. Al2 O3 nanoparticles and CMC was selected as nucleating agents and thickener. CH3COONa·3H2 O–8%KCl with 1 wt.% Al2 O3 nanoparticles and 4 wt.% CMC show an excellent performance. Abstract: The phase change performance of the CH3 COONa·3H2 O–KCl composites salt system with Al2 O3 nanoparticles and carboxyl methyl cellulose (CMC) were investigated in this paper. The CH3 COONa·3H2 O–KCl composite salt system was prepared by adding KCl (at 2, 4, 6, 8, and 10 wt.%) to CH3 COONa·3H2 O, respectively. Al2 O3 nanoparticles were proposed as the nucleating agent and CMC was selected as a thickening agent for the CH3 COONa·3H2 O–8 wt.%KCl composites salt system. The results show CH3 COONa·3H2 O–8 wt.%KCl composites salt system with 1 wt.% Al2 O3 nanoparticles and 4 wt.% CMC, in which almost no supercoiling phenomenon occurs. After 50 cycles of the melting–freezing cycle test, aluminum oxide is uniformly dispersed in SAT composites matrix, the latent heat remained constant at about 232.29 J/g. The maximum deviations of latent heat of composites CH3 COONa·3H2 O–8 wt.%KCl with 1 wt.% Al2 O3 nanoparticles and 4 wt.% CMC before and after the fifty-run-recycling test are only 3.6%.